Early metallurgy in Iberia and the western Mediterranean - Bartelheim, Martin; Pearce, Mark (Oxford University Press, 2015)
This chapter explores early metallurgy and metalwork in Iberia and the western Mediterranean, focusing on the metal-using phase known as ‘Chalcolithic’. After providing a background on the Iberian peninsula and its potential importance for early metallurgy, the discussion turns to the earliest treatment of copper ores in the region and the socioeconomic context of early metallurgy. It then looks at the earliest use of copper artefacts in Italy and the Italian peninsula c. 4500–3500 BC, as well as Mediterranean France. Finally, it examines the social role played by copper artefacts and metallurgy in the late Neolithic and Chalcolithic societies of the western Mediterranean.